Ilexonin a promoted euglobulin lysis and inhibited platelets aggregations of guinea pig’s plasma - LIU Gui-de; HU Zhi-jun; ZHONG Chun-ning (Acta Pharmacologica Sinica, 2016)
Ilexonin A was injected ip to guinea pigs. After 30 min blood was collected from common carotid artery with 3.8% sodium citrate as anticoagulant. The plasma was taken to determine euglobulin lysis time (ELT). In siliconated tubes platelets rich/poor plasma(PRP/PPP) were differentiately obtained after 1000/3000 rpm. The ELT of normal saline control group and ilexonin A group were 13±0 and 0±0 min, respectively; the fibrinolysin units were 769 and>10,000 U, respectively (p